PO.5.98 Glomerular activity at second kidney biopsy predicts of end-stage kidney disease in a large multi-centric cohort of patients with active lupus nephritis. (27th September 2022) - Gasparotto, M; Gatto, M; Sinico, RA; Moroni, G; Iaccarino, L; Doria, A
Abstract : Purpose: To investigate second kidney biopsy as predictor of end-stage kidney disease (ESKD) in active lupus nephritis (LN). Methods: Patients with biopsy-proven LN (ISN/RPS 2003) who had undergone a second kidney biopsy between January 1990 and December 2018 were included. Clinical and histological findings at first and at second biopsy were analyzed with Cox proportional hazard models to predict ESKD, defined as start of kidney replacement therapy. Survival curves were calculated with Kaplan-Meier method. Results: Ninety-two LN patients were included, 87% females, mean follow-up 17.9±10.1 years. Reasons for second kidney biopsy encompassed nephritic flares (n=28, 30.4%), proteinuric flares (n=46, 50.0%) or lack of renal response (n=18, 19.5%). A distinct group of 16 patients undergoing second renal biopsy as per protocol after achievement of at least partial renal response at 6 months or complete response at 12 months (defined according to EULAR criteria) were separately investigated. Class switch from first biopsy occurred in 50.5% of cases, mainly from non-proliferative towards proliferative classes. Class IV remained stable in over 50.0% of cases. Twenty-five patients (27.2%) developed ESKD, mostly belonging to the nephritic flare group (17/28, 60.7%). Independent predictors of ESKD at second biopsy were activity index (AI; HR 95% CI 1.20 [1.03–1.41], p=0.022), chronicity index (CI; 1.41 [1.09–1.82], p=0.008) and 24h-proteinuria (1.22 [1.04–1.42], p=0.013). AI≥2 (log-rank p=0.03), CI>4 (log-rank p=0.001), or proteinuria≥3.5 g/day (log-rank=0.009) identified thresholds for higher ESKD risk. In a subgroup analysis exploring itemized scoring for renal histology, glomerular activity and tubular chronicity mostly accounted for AI and CI association with ESKD (1.38 (1.03–1.86, p=0.032 and 1.62 (0.92–2.82), p=0.09, respectively). Within glomerular activity, presence of subendothelial deposits was independently associated with ESKD (4.8 (1.13–16.3) p=0.033). Conversely, no histological or laboratory predictors emerged at first biopsy (95%CI): AI: 0.88–1.19; CI:0.66–1.20; proteinuria 0.85–1.08. Within the protocol biopsy group, 18.7% developed ESKD. These patients displayed persistent histological activity at the second biopsy (AI>2), confirming that clinical remission does not invariably correspond to histological remission. Due to the small sample size, no independent predictors of ESKD in this group were identified. Conclusions: We show that both high activity and chronicity at second, but not at first kidney biopsy predict ESKD in patients with LN and lack of response or flaring after standard therapy. Besides, proteinuria is confirmed as an independent damaging factor for the kidney which may benefit from additional normalizing approaches. Patients reaching a renal clinical response may harbor active histological lesions which likely impact on their long-term prognosis. Altogether, our data identify easy-to-interpret parameters at second kidney biopsy which may significantly affect patient outcome, submitting repeated biopsy as a useful tool to improve prognostic stratification and prevent long-term deterioration of renal function.